Connecting Evaluation and Budgeting - Robinson, Marc (Independent Evaluation Group, World Bank Group, Washington, DC, 2014)
This paper discusses how evaluation is an essential tool for good budgeting and a core element of any well-designed government wide performance budgeting system. It is organized into 5 sections: (1) Evaluation and performance budgeting- the principle outlines the role which evaluation should, in principle, play in supporting good budgeting. It identifies the key ways performance information in general supports budgeting and then outlines the way performance budgeting seeks to structure the contribution of performance information to budgeting. The section concludes by discussing the nature and role of evaluation as a key component of the performance information base for budgeting. (2) Evaluation and performance budgeting in practice reviews the actual relationship between evaluation and performance budgeting by looking at the experiences of countries that have made substantial efforts to implement both. (3) Recent Efforts to Connect Evaluation and Budgeting discusses the global financial crisis, renewed interest in the role of evaluation as a budgetary tool is increasingly apparent among OECD countries, with countries such as the United States and the Netherlands making moves in this direction. (4) How to Better Connect Evaluation and Budgeting requires two things. First, evaluation needs to be made more useful for budgeting. Second, the budget process needs to focus more on expenditure prioritization and performance. (5) Conclusions.